The effect of muscle energy technique on pain, kinesiophobia, and quality of life in patients with COPD with chronic pain - Serpil Mıhçıoğlu; Mehtap Malkoç (Scientific Reports)
Abstract Patients with Chronic Obstructive Pulmonary Disease (COPD) experience pain both as a symptom and comorbid condition. This study aimed to investigate the effect of the Muscle Energy Technique (MET) on pain, kinesiophobia, and quality of life in patients with chronic pain and COPD. 52 patients with moderate COPD and pain complaints were included in this randomized controlled trial and longitudinal study and were divided into two groups. The intervention group received MET 3 times a week for 4 weeks, while the control group was given a home exercise program. Both groups participated in a home-based exercise program. Pain, fear of movement, and health-related quality of life were assessed at baseline, the end of the 4-week intervention, and at the 6-week follow-up. Significant improvements were observed in both groups; however, the intervention group showed more pronounced reductions in pain and kinesiophobia as well as improvements in quality of life (p < 0.05), and the effectiveness decreased over time. This study highlights the potential benefits of MET for pain, kinesiophobia, and quality of life in patients with chronic pain and COPD. Therefore, MET interventions should be considered in the treatment of chronic pain in patients with COPD. Trial registration: NCT04874571.